(untitled) (Journal of actual problems of jurisprudence, 2018)
Legal responsibility for water violations is an actual problem of legal science. With the development of legal science approaches to the content, performance and other features of the legal responsibilities have changed. Traditionally, the legal responsibility for the violation of water legislation are classified by industry sector, that criminal, administrative, civil and disciplinary. Keywords: water offense, the legal responsibility for the violation of water legislation, water crimes, water misdemeanors.